Pengaruh Karakteristik Perusahaan Terhadap Lamanya Penyelesaian Audit (Audit Delay) (Studi Empiris pada Perusahaan Food And Beverage yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019) - Friska Yuliana; Riana Rachmawati Dewi; Rosa Nikmatul Fajri (Universitas Batanghari Jambi, 2021)
This study aims to test and analyze the influence of company size, KAP size, profitability, solvency and audit committee on audit delay. The population in this research is a food and beverage manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This type of research is quantitative research. Sampling with purposive sampling technique resulted in 15 food and beverage manufacturing companies in 2017-2019 according to the specified criteria, resulting in 45 research data obtained. This study used multiple linear regression analysis. The results of this study concluded that the profitability and solvency have an effect on audit delay. While the size of the company, size of KAP and audit committee has no effect on audit delay.